Serum miR-181b-5p predicts ascites onset in patients with compensated cirrhosis - Ana Garcia Garcia de Paredes (Elsevier, 2021)
Background & Aims: Treatment with non-selective beta-blockers (NSBBs) reduces the risk of ascites, which is the most common decompensating event in cirrhosis. This study aimed to assess the ability of a serum microRNA (miRNA) signature to predict ascites formation and the hemodynamic response to NSBBs in compensated cirrhosis. Methods: Serum levels of miR-452-5p, miR-429, miR-885-5p, miR-181b-5p, and miR-122-5p were analyzed in patients with compensated cirrhosis (N = 105). Hepatic venous pressure gradient (HVPG) was measured at baseline, after intravenous propranolol, and 1 year after randomization to NSBBs (n = 52) or placebo (n = 53) (PREDESCI trial). miRNAs were analyzed at baseline and at 1 year. Results: Nineteen patients (18%) developed ascites, of whom 17 developed ascites after 1 year. miR-181b-5p levels at 1 year, but not at baseline, were higher in patients that developed ascites. The AUC of miR-181b-5p at 1 year to predict ascites was 0.7 (95% CI 0.59–0.78). miR-429 levels were lower at baseline in acute HVPG responders to NSBBs (AUC 0.65; 95% CI, 0.53–0.76), but levels at baseline and at 1 year were not associated with the HVPG response to NSBBs at 1 year. Conclusions: Serum miR-181b-5p is a promising non-invasive biomarker to identify patients with compensated cirrhosis at risk of ascites development. Lay summary: Ascites marks the transition from the compensated to decompensated stage in cirrhosis and indicates a worsening in prognosis. There are currently no easily accessible tools to identify patients with compensated cirrhosis at risk of developing ascites. We evaluated the levels of novel molecules termed microRNAs in the blood of patients with compensated cirrhosis and observed that miR-181b-5p can predict which patients are going to develop ascites.